Sensibilidades compartilhadas na imprensa árabe diaspórica: reflexões sobre nacionalismo árabe e 'nasserismo' em "O Oriente" - Meinberg Garcia, Luís Augusto (2025)
This article analyzes the magazine O Oriente, edited by Mussa Kuraiem between 1927 and 1974, an important vehicle for the Arab press in Brazil, as a means of cultural and political mediation in the production and adaptation of Arab subjectivities in a diasporic context. By addressing Arab nationalism as a tradition in constant transformation, the text explores how the magazine seeks to play a central role in shaping Arab subjectivities in Brazil. Through the circulation of political and cultural discourses, O Oriente not only serves as a platform for cohesion within the Arab community in São Paulo but also as a space for negotiation between Arab traditions and the demands of the Brazilian context, offering its readers a way to connect with their cultural roots while simultaneously adapting to local dynamics, producing Arab sensibilities in Brazil as an ongoing process of mediation between past and present. The article thus discusses how the magazine relies on a pan-Arabist ideology aimed at the integration of Arabs in both international and Brazilian contexts, drawing on secular and progressive ideals, which reflect the exacerbation and re-signification of Arab nationalism, particularly following the creation of the United Arab Republic (1958) and the interpretation of 'Nasserist' ideals.